Mobile Golf Scoring System - Al-Qudah, Hasan Mohammad Adnan Hasan (2007)
The rapid deployment of mobile technology has increasingly provided people and organizations with the ability to work away from office. The mobile technology was developed to create ubiquitous environment where information can be accessed in any place and at any time. In the golf game, the golfers can only know their overall standing position after they had finished playing the game, where it would be little late for them to change their strategy in order to change their scores in the game. Knowing the score of the other golfers is important in the strategy of game play either playing "safe game" or "playing an aggressive game". The major aim of this research is to provide the golfer with information about his/her status during the game. The research is targeted to UUM Golf club. The System Development Life Cycle (SDLC) has been implemented in various applications and it is considered the general methodology of developing this current system. This paper reports on the steps to build and implement a mobile golf scoring system prototype.